Answer:
(fog)(-3)= 11
Step-by-step explanation:
we have from statement:
f(x) = 7x + 4
g(x) = x + 4
so we have:
(fog)(x)= 7(x+4) + 4
(fog)(-3)= 7(-3+4) + 4
(fog)(-3)= 7(1) + 4
(fog)(-3)= 11
Answer:
14 and 6
Step-by-step explanation:
Let's start by naming the first number x.
We can name the second number y.
We can set up equations to model our situation.
x+y=2x-8
x-y=2y-4
Let's simplify the equations.
x+y=2x-8
Subtract 2x from both sides
-x+y=-8
__________
x-y=2y-4
Subtract 2y from both sides.
x-3y=-4
Add the two equations together to eliminate x.
x-3y=-4
-x+y=-8
________
0x-2y=-12
-2y=-12
Divide both sides by -2.
y=6
The second number is 6.
Plug that back in.
x+6=2x-8
Subtract x from both sides
6=x-8
Add 8 to both sides
x=14
The first number is 14
<u>f(x) = x + 3</u>
f(2) = 2 + 3
f(2) = 5
f(4) = 4 + 5
f(4) = 9
f(6) = 6 + 5
f(6) = 11
{(2, 5), (4, 9), (6, 11)}
You find the area of one side of the cube which is 12.25 mm and multiply it by the number of side which is 6. and the answer is 73.5 mm
Answer:
-32
Step-by-step explanation:
=(-2)^5
=-2*-2*-2*-2*-2-2
-2*-2=4
-2*-2=4
-2
4*4=16
16*-2=-32
Hope this helps :) ❤❤❤